1998
DOI: 10.1161/01.atv.18.7.1061
|View full text |Cite
|
Sign up to set email alerts
|

Two Major Loci Control Variation in β-Lipoprotein Cholesterol and Response to Dietary Fat and Cholesterol in Baboons

Abstract: Abstract-We explored the genetic control of cholesterolemic responses to dietary cholesterol and fat in 575 pedigreed baboons. We measured cholesterol in ␤-lipoproteins (low density lipoprotein cholesterol [LDLC]) in blood drawn from baboons while they were consuming a baseline (low in cholesterol and fat) diet, a high-saturated fat (lard) diet, and a high-cholesterol, high-saturated fat diet. In addition to baseline levels (LDLC Base ), we analyzed two variables for diet response: LDLC RF , which represents t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

1999
1999
2009
2009

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 41 publications
1
21
0
Order By: Relevance
“…Our estimates of residual heritability are consistent with previous findings from different researchers also describing the substantial effect of genes on Lp-PLA 2 [5,13] and LDL-C concentration [7,8].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Our estimates of residual heritability are consistent with previous findings from different researchers also describing the substantial effect of genes on Lp-PLA 2 [5,13] and LDL-C concentration [7,8].…”
Section: Discussionsupporting
confidence: 91%
“…In studies of humans and animals, genes have been shown to account for a moderate proportion of the variance − 36% to 59% -in LDL-C levels [7,8]. Published genome scans have mapped quantitative trait loci (QTLs) affecting LDL-C concentration in humans to multiple chromosomal regions that harbor candidate genes affecting the regulation of LDL metabolism, processing and transport [7,9,10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As previously described, 13 all baboons were subjected to the same dietary challenge, and serum samples were available on each animal on each of 3 diets: (1) basal diet, a baseline monkey diet (Wayne Teklad) that was low in fat (Ϸ4% of calories) and cholesterol (0.03 mg/kcal); (2) HCHF diet, a diet high in saturated fat (40% of calories from fat by the addition of lard) and cholesterol (1.7 mg/kcal); and (3) LCHF diet, a high fat-only diet (40% of calories from lard, 0.03 mg/kcal of cholesterol).…”
Section: Dietary Protocolmentioning
confidence: 99%
“…LDLC was assayed on all diet samples, and LDLC RC was calculated as the difference in LDLC between the HCHF and LCHF diets (LDLC HCHF ϪLDLC LCHF ). 13 Published human primers were used to amplify 279 homologous microsatellite loci from baboon genomic DNA samples. 14,15 Approximately two thirds of the genotypes and 236 of these highly polymorphic markers were generated by researchers at Axys Pharmaceuticals Inc and were used to develop the baboon genomic map.…”
Section: Assay Of Ace Ldlc and Genotypesmentioning
confidence: 99%